2019
DOI: 10.3390/children6010011
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Peer Victimization among Middle and High School Students

Abstract: Peer victimization at school is a pressing public health issue. Peer victimization has a deleterious impact on the victim and can lead to lifelong negative outcomes such as depression. The purpose of the present study is to examine peer victimization and potential individual, school, and peer correlates in a national sample of middle and high school students. A secondary data analysis of the School Crime and Safety survey was conducted to investigate study aims. Greater than one in 20 (7.2%) of students report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
5
1
Order By: Relevance
“…The correlation between peer attachment and perceived school climate in this study was particularly neglectable (r = .007). It is in opposite with several similar previous studies (Acosta, Chinman, Ebener, Malone, Phillips & Wilks, 2019;Vidourek & King, 2019). Greater peer attachment among the students is supposed to be resulted from the positive evaluation of their school climate and in return, it indicates a succesful transmission of values from the school to the students.…”
Section: Discussioncontrasting
confidence: 85%
“…The correlation between peer attachment and perceived school climate in this study was particularly neglectable (r = .007). It is in opposite with several similar previous studies (Acosta, Chinman, Ebener, Malone, Phillips & Wilks, 2019;Vidourek & King, 2019). Greater peer attachment among the students is supposed to be resulted from the positive evaluation of their school climate and in return, it indicates a succesful transmission of values from the school to the students.…”
Section: Discussioncontrasting
confidence: 85%
“…Exposure to bullying and violence at school takes place at all student ages and has detrimental effects on students' psychosocial development and behavioral health (Chen & Chen, 2020;Chen & Wei, 2011Cho, 2019;McDougall & Vaillancourt, 2015;Moore et al, 2017;Reijntjes, Kamphuis, Prinzie, & Telch, 2010;Ttofi, Bowes, Farrington, & Lösel, 2014;Ttofi, Farrington, Losel, Crago, & Theodorakis, 2016). In past decades, a substantial body of research has been conducted to identify various factors increasing students' likelihood of being exposed to school violence and bullying (i.e., risk factors for school bullying victimization) (Chen & Astor, 2010;Chen, Wu, Chang, & Wei 2020a;Chen, Wu, & Wei, 2020b;Hong et al, 2016;Schreck, Miller, & Gibson, 2016;Vidourek & King, 2019;Wei, Chang, & Chen, 2016;Wynne & Joo, 2011). These studies have provided rich information to school practitioners and policy makers to design intervention programs and strategies to reduce students' likelihood of being victimized, through eliminating the identified risk factors or effects (Chen & Chen, 2018;Gaffney, Ttofi, & Farrington, 2019;Zych, Ortega-Ruiz, & Del Rey, 2015a, b).…”
Section: Introductionmentioning
confidence: 99%
“…The current research also revealed that positive mental health and resilience was significantly associated with a reduced risk of suicidality and self-harm in both types of bullying victims, and this was corroborated by the previous studies, 16 perhaps because adolescents tend to spend more time with friends and increasingly rely on support from friends at this age. 42 Moreover, although previous meta-analyses 22,43 reported mixed results, this study found that adequate sleep (8-12 hours/day) was positively related with the reduced risk of suicidality and self-harm in bullying victims. One possible explanation is that insufficient sleep may play a role in impairing social connectedness and may subsequently increase depression in an individual and may lead to suicidality and self-harm.…”
Section: Discussionmentioning
confidence: 52%
“…16,39 Interestingly, the results did not find any significant association of school connectedness with suicidality and/or self-harm in any bullying victim groups, although a recent study conducted in the US reported that low school connectedness are a potential risk factor for bullying victimization. 42,44 Although the current study utilized a nationwide survey, providing converging evidence for risk and protective factors of suicidality and self-harm in bullying victims (traditional and cyber), the study has some limitations. This cross-sectional data was restricted to 2125 children aged between 14-to 17year-olds, and data were collected in the year between 2013-14; thus, caution should be exercised before generalizing these results in later years to other age groups (e.g., adults) and for the entire country of Australia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation